Calculation:

Consider, the equation, \(\displaystyle{y}={5}-{\left({6}—{x}\right)}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={5}-{\left({6}-{x}\right)}\)

Opening the bracket, multiply by -1, this gives,

\(\displaystyle{0}={5}-{6}+{x}\)

\(\displaystyle{0}=-{1}+{x}\)

\(\displaystyle{x}={1}\)

So, the x-intercept is (1,0).

To compute y-intercept, put \(\displaystyle{x}={0}\).

\(\displaystyle{y}={5}-{\left({6}-{0}\right)}\)

\(\displaystyle{y}={5}-{6}\)

\(\displaystyle{y}=-{1}\)

So, the y -intercept is (0, -1).

Hence, the x and y -intercepts of \(\displaystyle{y}={5}-{\left({6}-{x}\right)}\) are (1,0) and (0,-1),respectively.

Consider, the equation, \(\displaystyle{y}={5}-{\left({6}—{x}\right)}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={5}-{\left({6}-{x}\right)}\)

Opening the bracket, multiply by -1, this gives,

\(\displaystyle{0}={5}-{6}+{x}\)

\(\displaystyle{0}=-{1}+{x}\)

\(\displaystyle{x}={1}\)

So, the x-intercept is (1,0).

To compute y-intercept, put \(\displaystyle{x}={0}\).

\(\displaystyle{y}={5}-{\left({6}-{0}\right)}\)

\(\displaystyle{y}={5}-{6}\)

\(\displaystyle{y}=-{1}\)

So, the y -intercept is (0, -1).

Hence, the x and y -intercepts of \(\displaystyle{y}={5}-{\left({6}-{x}\right)}\) are (1,0) and (0,-1),respectively.